2004
DOI: 10.1354/vp.41-2-141
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lymphocytes in Canine Gastrointestinal Lymphoma

Abstract: Abstract. Primary canine gastrointestinal lymphoma has been believed to be of B-cell origin based on the morphology and behavior of the neoplastic cells and the evidence from the human medical field. However, the neoplasms have not to date been characterized as to the origin of the cell population. Forty-four cases diagnosed as canine gastrointestinal lymphoma were retrieved from the records of the Veterinary Teaching Hospitals at the University of Minnesota and the University of Wisconsin-Madison. Four of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
76
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 14 publications
11
76
1
1
Order By: Relevance
“…This is correlated with other recent studies suggesting that most digestive tract lymphomas in dogs come from T lymphocytes and often have epitheliotropism (Coyle and Steinberg, 2004;Ozaki et al, 2006).…”
Section: Resultssupporting
confidence: 91%
“…This is correlated with other recent studies suggesting that most digestive tract lymphomas in dogs come from T lymphocytes and often have epitheliotropism (Coyle and Steinberg, 2004;Ozaki et al, 2006).…”
Section: Resultssupporting
confidence: 91%
“…38 Other studies identified between 63% and 75% of gastrointestinal lymphomas as having a T-cell phenotype, but these studies also examined the stomach, which is known to have a higher incidence of B-cell lymphomas in dogs and cats. 4,11,20,39,44 The only statistically significant morphologic parameter for differentiating IBD from lymphoma was the presence of intraepithelial infiltrations in both surface and crypt epithelium. In contrast to cats, a significant number of dogs with a diagnosis of IBD based on the combined HE, IHC, and PARR results exhibited marked intraepithelial infiltrates.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to humans (Sagaert et al 2012), most cases of primary GI lymphomas in dogs are of T-cell origin (Couto et al 1989;Coyle and Steinberg 2004). Carrasco et al (2015) reported a 100% prevalence of T-cell alimentary lymphomas, but the samples were taken from duodenum only.…”
Section: Discussionmentioning
confidence: 98%
“…The small intestine is most frequently involved, followed by the stomach (Coyle and Steinberg 2004).…”
mentioning
confidence: 99%